2013
DOI: 10.4103/0378-6323.116735
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of consistency in diagnostic accuracy of teledermatology tools

Abstract: SAFT and VC were adequately validated on a large number of patients by various feasibility studies with the gold standard (face-to-face) comparison between teledermatologists and clinical dermatologists. The DA of SAFT was good, stable over the 15 years and comparable to VC. Health-care providers need to plan for appropriate utility of SAFT either alone or in combination with VC to implement and deliver teledermatology care in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…a large (>100 subjects) prospective study without a gold standard comparison. [ 14 ] The present study showed that 10 common diagnoses account for more than three-fourths of the skin disorders encountered in primary healthcare clinic. The PCPs thus need to be trained on these 10 common skin conditions so that they can appropriately manage a large proportion of patients with common dermatologic complaints.…”
Section: Discussionmentioning
confidence: 69%
“…a large (>100 subjects) prospective study without a gold standard comparison. [ 14 ] The present study showed that 10 common diagnoses account for more than three-fourths of the skin disorders encountered in primary healthcare clinic. The PCPs thus need to be trained on these 10 common skin conditions so that they can appropriately manage a large proportion of patients with common dermatologic complaints.…”
Section: Discussionmentioning
confidence: 69%
“…This makes it ideal for the utilization of virtual medicine. In India, Kantiraj et al validated the store and forward teledermatology and videoconferencing in a large number of patients while using gold standard (face-to-face) comparison between teledermatologists and clinical dermatologists [40]. Nair and Nair also reported that teledermatology is a viable alternative to face to face encounters via both store and forward and videoconferencing options.…”
Section: Involvement Of Private Enterprise In the Field Of Telemedicimentioning
confidence: 99%
“…The diagnostic accuracy for general teledermatology practice using store and forward, video conference and mobile teledermatology tools is 73%, 70% and 70% respectively. The diagnostic accuracy for subspecialty teledermatology for pediatric and geriatric is 65% and 88% respectively 15 . Several studies have demonstrated acceptable diagnostic accuracy for various teledermatology tools.…”
Section: Introduction Introductionmentioning
confidence: 99%
“…[3] A recent longitudinal study analyzed the diagnostic accuracy of various teledermatology tools and recommended that plans for implementing a teledermatology practice could be based on this classification. [15] The dermatology conditions that were classified for teledermatology practice as a) Regular teledermatology practice b) tertiary teledermatology practice and c) subspecialty (pediatric and geriatric) teledermatology practice. [15] The advantage is assessment of feasibility and diagnostic accuracy with respect to each subdivision of teledermatology practice could be audited and analyzed for implementation.…”
Section: Introduction Introductionmentioning
confidence: 99%
See 1 more Smart Citation